The Multi-Annual Residency of Juvenile Smooth Hammerhead Shark in an Oceanic Island Nursery - Afonso, Pedro; Gandra, Miguel; Graça, Gonçalo; Macena, Bruno; Vandeperre, Frederic; Fontes, Jorge (Frontiers in Marine Science, 2022)
The increased risk of local extinction becomes critical for sharks depending on the narrow and isolated coastal habitats of oceanic islands. This includes large pelagic oceanic sharks that use these habitats as nurseries, as hypothesized for the least known of cosmopolitan large hammerhead sharks, Sphyrna zygaena. We used a combination of acoustic and satellite telemetry in a juvenile population of Faial and Pico islands, Azores, mid-north Atlantic, to confirm if this isolated archipelago holds nurseries, and to answer questions related to their function and spatial-temporal stability. Our long-term acoustic tracking data showed a cluster of individual core home ranges in specific areas of north shore Faial, and surface-positions from five SPOT tagged individuals also showed a clustering in those areas for up to 1 year. These patterns seem reveal a true habitat preference within the Faial-Pico island (sub) population of juvenile smooth hammerhead shark, and thus constitutes hard evidence for this area to be considered a nursery. Some individuals used this nursery for up to 4 years, especially during summers. Sharks also showed a strong a diel behavior, typically using the inshore nurseries during the day and moving further offshore during the night, during which they increase activity and dive deeper, most possibly to feed. We speculate that a combination of increased feeding opportunities, expanded trophic niche and reduced predatory pressure may be a key evolutionary driver for the existence, prolonged use and even preference of coastal nurseries at oceanic islands by juvenile smooth hammerhead shark. Given that these nurseries may constitute Essential Fish Habitat (EFH) for this species, they should be explicitly included in spatial management measures at the local and regional scales, as they may also play a role of greater importance to the north Atlantic population of this oceanic species.